Keabsahan Sertipikat Hak Tanggungan Elektronik dalam Prospek Pejabat Pembuat Akta Tanah - Socialista, Tembang Merah Sunny; Putri, Arsella Imanda; Fernando, Dadang (Faculty of Law, Diponegoro University, 2025)
The policy on Electronic Mortgage Rights (HT-el), brings a series of legal consequences, where the Mortgage Right certificate was originally in physical form with the HT-el policy, the certificate is issued in electronic form. The HT-el policy also has legal implications in relation to the authority of the Land Deed Making Officer (PPAT) in Indonesia. Based on these problems, this study aims to analyze the validity of the mortgage certificate issued by the National Land Agency (BPN) in the HT-el policy procedure and its consequences for the prospects of PPAT. This study will examine the regulation of the electronic mortgage policy still using APHT which is made conventionally by PPAT with a digital signature, which is then scanned and the scan results are used by the land office to make and issue mortgage certificates to the public. In addition, this study will also discuss the prospects of PPAT in the form of challenges and opportunities faced as a result of the HT-el policy. The results of the study indicate that the HT-el policy requires improvement to ensure the validity of the mortgage certificate to provide legal certainty to the public, as well as to protect the interests of the parties involved.